Motivation in Language Learning Process - AbdAlgane Mohammed, Mohammed AbdAlla (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2020)
There are a lot of factors which influence success in language learning. However, one of the most important factors is the learner’s motivation to learn the language in order to be able to use it in real-life situations. Research and experience show that learners with strong motivation can achieve a lot regardless of circumstances. Studies of motivation in second language learning have led to several distinctions, one of which is the distinction between integrative and instrumental motivation. According to this distinction, some learners are motivated to learn the language because they want to integrate into the target language community, while for others the driving force is their desire to achieve personal goals. Another distinction related to motivation is the distinction between extrinsic motivation, which is regulated from an external source, and intrinsic motivation, which is regulated from within. And according to a third distinction, there can be global, situational and task motivation. Even though teachers cannot control all types and aspects of motivation, they can do a lot to help learners develop motivation and interest for learning the language. This paper discusses the importance of motivation, the different types of motivation and the ways of promoting learner motivation and interest.